Absolute politics and judicious pragmatism: political culture in democratization by reforma. Issue 3 (16th April 2017) - Tzortzis, Ioannis
ABSTRACT: Comparing the political cultures of Spain and Greece before and during the dictatorships, the article seeks to explain the different outcomes of the regimes' self-transformation attempts, the one that succeeded (Spain) and the other that failed (Greece, the little-known "Markezinis experiment"). Its position is that the abandoning of hard-line ideological stances that have been called "absolute politics", which was the main contributor to the Spanish Reforma's success, did not work in Greece due to the persistence of the post-civil war and pre-dictatorial cleavages in both elites and civil society, thus rendering the mellowing of confrontation lines and the consensual politics necessary for the negotiations and mutual concessions between elites and counter-elites unfeasible. The result was, in contrast to the Spanish reforma Pactada, a reverse to authoritarianism perpetrated by the hard-line officers, prolonging the regime for eight crucial months.